2000
DOI: 10.1309/q4ae-bmcw-cq7j-nuvt
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unfractionated Heparin, Low-Molecular-Weight Heparin, and Heparinoid on Thromboelastographic Assay of Blood Coagulation

Abstract: Thromboelastography (TEG) has been used increasingly as an intraoperative hemostasis monitoring device. Low-molecular-weight heparins are given increasingly to reduce the development of antibodies against the heparin-platelet factor 4 complex, and heparinoids are given to patients who have developed the antibody. We studied the effect of unfractionated heparin, a low-molecular-weight heparin (enoxaparin sodium [Lovenox]), and a heparinoid (danaparoid sodium [Orgaran]) on blood clotting assayed with TEG (TEG cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
65
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 21 publications
8
65
0
2
Order By: Relevance
“…[7][8][9][10][11] In addition, several studies have specifically evaluated the utility of TEG as a surrogate monitor of LMWH therapy in humans, albeit with contrasting results. [7][8][9] This study established a reference range for TEG parameters for healthy cats and demonstrated an effect of heparin therapy on TEG. However, in the current study, only UFH had a significant effect on TEG when R values were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] In addition, several studies have specifically evaluated the utility of TEG as a surrogate monitor of LMWH therapy in humans, albeit with contrasting results. [7][8][9] This study established a reference range for TEG parameters for healthy cats and demonstrated an effect of heparin therapy on TEG. However, in the current study, only UFH had a significant effect on TEG when R values were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Klein et al [9] analyzed the relationship of thromboelastography and serum anti-Xa levels in postoperative patients treated with the LMWH and enoxaparin and found that the value of thromboelastography significantly correlates with the levels of anti-Xa activity and the degree of anticoagulation produced by low molecular weight heparin. Zmuda et al [10] studied the effect of unfractionated heparin, and a heparinoid on blood clotting assayed with TEG in vitro and the efficacy of protamine sulfate and heparinase for reversing the effect.…”
Section: Introductionmentioning
confidence: 99%
“…Using thromboelastography (TEG), reversal of enoxaparininduced prolongation of clotting by heparinase was used to detect enoxaparin concentrations of 0.2 anti-Xa IU/ml or greater; however, there were inconsistencies among the different assay parameters (R, k and a) [13]. In a more recent study with TEG, there was a marked loss in linearity between LMWH concentration and reaction time (time to beginning of clot formation, R) at concentrations of LMWH above 0.5 IU/ml.…”
Section: Discussionmentioning
confidence: 99%